The elements of graphical statics and their application to framed structures : with numerous practical examples of cranes - bridge, roof and suspension trusses; braced and stone arches - pivot and draw spans - continuous girders, together with the best methods of calculation, and containing also new and practical formulae for the pivot or draw span - braced arch - continuous girder, etc - Du Bois, A. Jay 1849-1915 (ICE Publishing, 1875)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present.